Factors Affecting High Caries Risk in Children With and Without Cleft Lip and/or Palate: A Cross-Sectional Study. (September 2021) - Chaudhari, Prabhat Kumar; Kharbanda, Om P.; Chaudhry, Rama; Pandey, Ravindra Mohan; Chauhan, Shashank; Bansal, Kalpana; Sokhi, Ramandeep Kaur
Objective: The aim of the study was to analyze the caries protective factors, salivary parameters, and microbial counts in high caries risk children with cleft lip and/or palate (CL/P). Design: This was a cross-sectional study. Setting: This study was conducted in a tertiary health care teaching hospital in New Delhi, India. Participants: The study was conducted in 40 children, 20 with CL/P and 20 without aged between 5 and 12 years. Methods: Children with 2 or more caries lesions in both groups were included in this study. Demographic details, dental caries of affected teeth (World Health Organization criteria for Decayed Missing Filled Teeth [WHO-DMFT] and International Caries Detection and Assessment System [ICDAS II]), caries protective factors, salivary parameters, and microbial counts were recorded by one calibrated investigator. Main Outcome Measures: Caries protective factors, salivary parameters, and microbial profile. Results: The Chi-square (χ 2 ) test and Pearson correlation were used for statistical analysis. All the children participating in the study brushed their teeth only once in a day and consumed sweets more than twice a day. None of the children had ever received fluoride varnish. Resting saliva had a low buffering capacity in 80% of children with CL/P and 95% of children without CL/P. Microbial assessment of stimulated saliva showed that with the increases in the numbers (DMFT scores ≥4) and severity (ICDAS codes from 1-2 to 5-6) of caries lesions, both Streptococci and Lactobacilli counts were ≥10 5 colony-forming units/mL of saliva in the both groups. Conclusions: Children with CL/P showed limited access to caries protective measures and low buffering capacity in resting saliva, along with elevated levels of salivary Streptococci and Lactobacilli in stimulated saliva.